2018
DOI: 10.1074/jbc.ra118.001885
|View full text |Cite
|
Sign up to set email alerts
|

Acute loss of iron–sulfur clusters results in metabolic reprogramming and generation of lipid droplets in mammalian cells

Abstract: Iron-sulfur (Fe-S) clusters are ancient cofactors in cells and participate in diverse biochemical functions, including electron transfer and enzymatic catalysis. Although cell lines derived from individuals carrying mutations in the Fe-S cluster biogenesis pathway or siRNA-mediated knockdown of the Fe-S assembly components provide excellent models for investigating Fe-S cluster formation in mammalian cells, these experimental strategies focus on the consequences of prolonged impairment of Fe-S assembly. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
77
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 68 publications
15
77
1
Order By: Relevance
“…Fe-S cluster biosynthesis occurs at a multiprotein complex consisting in part of the cysteine desulfurase (NFS1) and Fe-S scaffold protein (ISCU; Johnson et al, 2005). Loss of either compromises cluster biosynthesis and is associated with mitochondrial defects (Fosset et al, 2006; Crooks et al, 2018). Therefore, we introduced shRNAs targeting either NFS1 or ISCU (Alvarez et al, 2017) to establish the effects of disrupting Fe-S cluster biosynthesis on the respiratory chain and ACO2.…”
Section: Resultsmentioning
confidence: 99%
“…Fe-S cluster biosynthesis occurs at a multiprotein complex consisting in part of the cysteine desulfurase (NFS1) and Fe-S scaffold protein (ISCU; Johnson et al, 2005). Loss of either compromises cluster biosynthesis and is associated with mitochondrial defects (Fosset et al, 2006; Crooks et al, 2018). Therefore, we introduced shRNAs targeting either NFS1 or ISCU (Alvarez et al, 2017) to establish the effects of disrupting Fe-S cluster biosynthesis on the respiratory chain and ACO2.…”
Section: Resultsmentioning
confidence: 99%
“…This deviation is potentially attributable to the influence of ISCU but not NNT on protein lipoylation. Unlike the clusters associated with ACO2 or the respiratory chain, the 4Fe-4S cluster that mediates LIAS catalysis is consumed in the process to contribute sulfur for synthesis of lipoic acid (Parry and Trainor, 1978, Miller et al, 2000, Crooks et al, 2018. This activity permits lipoylation of components of PDH and a-ketoglutarate dehydrogenase, which are required for TCA cycling.…”
Section: Discussionmentioning
confidence: 99%
“…LIAS is required for lipoic acid synthesis and the eventual conjugation of crucial lipoate moieties to components of PDH (E2) and a-ketoglutarate dehydrogenase (dihydrolipoamide Ssuccinyltransferase, DLST), among others. LIAS is critically sensitive to disruptions in Fe-S cluster biosynthesis, as its resident Fe-S cluster is consumed during catalysis, imposing a requirement for continual cluster turnover (Crooks et al, 2018). Indeed, disruption of NFS1 and ISCU expression resulted in a substantial reduction in PDH-E2 and DLST lipoylation in PC9 cells (Fig.…”
Section: Fe-s Cluster Biosynthetic Machinery (Figs 5 a B And C)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these studies imply that hydrazonyl chlorides form fluorescent background products through nitrileimine‐independent mechanisms that tetrazoles do not engage in, such as direct hydrolysis (Figure S1 C). A notable feature of our strategy is that it is not limited to fumarate, but can potentially be used to detect the dysregulation of other metabolic dipolarophiles, including itaconate, gluaconate, and cis ‐aconitate, that accumulate in a variety of pathophysiological settings . Exploring these additional metabolite dipolarophiles, we found that cis ‐aconitate and itaconate also formed readily observable cycloadducts upon treatment with 1 (Figure S2), but were less detectible than fumarate (Figure E).…”
Section: Methodsmentioning
confidence: 99%